If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r = 3(r + -2) Reorder the terms: 4r = 3(-2 + r) 4r = (-2 * 3 + r * 3) 4r = (-6 + 3r) Solving 4r = -6 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 4r + -3r = -6 + 3r + -3r Combine like terms: 4r + -3r = 1r 1r = -6 + 3r + -3r Combine like terms: 3r + -3r = 0 1r = -6 + 0 1r = -6 Divide each side by '1'. r = -6 Simplifying r = -6
| 94=8j+30 | | y=4(x+6)-7 | | x-5/9=8/9 | | 5+4x+5+48= | | -3(t-4)+9t=8t-6 | | 60y^2+3y-36=0 | | x^2=14-7x | | 5(x-8)+26= | | 5x-4(4x-1)=2 | | -6x-142=2x+98 | | 5x+45+9x=180 | | 17=64-n | | i7n/9-62=5n/9-49 | | 31x=56 | | Y/3-4=-2 | | B/5-2=2 | | 4+-6+9=x | | .10x+12y=2990 | | a/4-b/3=5/12 | | -2+5n+3n^2=0 | | 10=30/z | | 9p-19=5(p-2)-2(7-2p) | | 5v-5v+v=16 | | Y=-4(6)-10 | | (14-2x)+40=180 | | -2x-10=-2x-10 | | x-10y=13 | | 1=k/10-1 | | x^2-14x-40= | | (14-2x)+40=90 | | 12x+6y= | | 2(-6p+7)+4(p+3)= |